The role of PML ubiquitination in human malignancies - Chen Ruey-Hwa; Lee Yu-Ru; Yuan Wei-Chien (Journal of Biomedical Science, 2012)
Abstract Tumor suppressors are frequently downregulated in human cancers and understanding of the mechanisms through which tumor cells restrict the expression of tumor suppressors is important for the prognosis and intervention of diseases. The promyelocytic leukemia (PML) protein plays a critical role in multiple tumor suppressive functions, such as growth inhibition, apoptosis, replicative senescence, suppression of oncogenic transformation, and inhibition of migration and angiogenesis. These tumor suppression functions are recapitulated in several mouse models. The expression of PML protein is frequently downregulated in diverse types of human tumors and this downregulation often correlates with tumor progression. Recent evidence has emerged that PML is aberrantly degraded in various types of tumors through ubiquitination-dependent mechanisms. Here, we summarize our current understanding of the PML ubiquitination/degradation pathways in human cancers. We point out that multiple pathways lead to PML ubiquitination and degradation. Furthermore, the PML ubiquitination processes are often dependent on other types of posttranslational modifications, such as phosphorylation, prolylisomerization, and sumoylation. Such feature indicates a highly regulated nature of PML ubiquitination in different cellular conditions and cell contexts, thus providing many avenues of opportunity to intervene PML ubiquitination pathways. We discuss the potential of targeting PML ubiquitination pathways for anti-cancer therapeutic strategies.